Answer: 1/4
Step-by-step explanation:
-
Answer:
-0.8/ -4/5
Step-by-step explanation:
5(m+1) -1 = 0
5m +5 -1 = 0
5m +4 =0
5m= -4
m= -4/5
Answer:
She should have substituted y = 17 - 2x in the first equation
Step-by-step explanation:
3x + 4y = 33
2x + y = 17
y = 17 - 2x
3x + 4(17 - 2x) = 33
3x + 68 - 8x = 33
5x = 35
x = 7
y = 17 - 2(7)
y = 3
x = 7, y = 3
Only one solution
DO NOT CLICK THE LINK THE OTHER PERSON WHO ANSWERED SAID. PLEASE DONT
For this case we have the following polynomial:
x2 + 6x + 8
We note that the polynomial can be rewritten as:
(x + 4) (x + 2)
Answer:
A common factor binomial for this case is given by:
(x + 4)
option B